Electronic Payment Systems for Communications Services - Balaišis, P.; Eidukas, D.; Gočelkienė, L. (Elektronika ir Elektrotechnika, 2009)
The structure of the electronic payment systems for communications services is presented. The analysis of traffic flow volumes and the algorithm of flow volumes. The distribution density of values in the big interval of time as well as the dynamics of densities and the dynamics of values are provided. The rational dislocation of payment collection systems is presented. The target function is developed, and the road section is described. Ill. 11, bibl. 5 (in English; summaries in English, Russian and Lithuanian).